Богослов, проповідник, літератор (до 410-річчя Петра Могили) - Репринцева, В. (Харків : Харківський університет, 2007)
До 410-річчя Петра Могили.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::Technology and culture; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Literature; Могила Петро; історія релігії; богослов; проповідник; літератор